Conservation agriculture: Concepts, worldwide experience, and lessons for success of CA-based systems in the semi-arid Mediterranean environments - Kassam A.; Friedrich T. (4. Rencontres Méditerranéennes du Semis Direct, 2011)
Conservation Agriculture (CA), comprising minimum mechanical soil disturbance and direct seeding, organic mulch cover, and crop diversification, is now practiced on more than 115 million ha in all continents and all ecologies, including the semi-arid Mediterranean environments. There is worldwide scientific evidence from research and empirical evidence from farmer practice to show that there are large productivity, economic, social and environmental benefits that can be harnessed through the adoption of CA practices in all semi-arid Mediterranean environments, including those in the CWANA region. However, CA is not being mainstreamed in any serious sense in the countries of the Mediterranean basin and of Central Asia region. CA represents a fundamental change in production system thinking and is counterintuitive, novel and knowledge intensive. Experience across many countries has shown that the adoption and spread of CA requires a change in commitment and behaviour of all concerned stakeholders. While adoption of CA under the given climatic conditions of the Mediterranean region might be more challenging, it is at the same time more urgent than in other climatic zones. For the farmers, a mechanism to experiment, learn and adapt is a prerequisite. For the policy-makers and institutional leaders, transformation of tillage systems to CA systems requires that they fully understand the large economic, social and environmental benefits CA offers to the producers and the society at large. Further, the transformation calls for a sustained policy and institutional support role that can provide incentives and required services to farmers to adopt CA practices and improve them over time. The CWANA region, its people and institutions, both public and private sector, have everything to gain from adopting CA as a basis for sustainable agricultural intensification and ecosystem management. The greater impact that can result from the adoption of CA as a matter of policy and good stewardship is that agriculture development in the Mediterranean region will become part of the solution of addressing regional and global challenges including resource degradation, land and water scarcity and climate change.
4. Actes des Rencontres Méditerranéennes du Semis Direct, 2010/05/03-05, Sétif (Algérie)